Peran Guru PAUD Dalam Pembelajaran Di Kelas Dengan Meningkatkan Kemampuan Kompetensi di Era Digital:Studi Kasus Di TK Umara Kids Pekanbaru - Surati Ningsih; Si Riani N. Nst; M. Fakhri Hafizh; Rita Kurnia; Asfi Yanti WE (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to explore the strategies used by early childhood education teachers to enhance their pedagogical competence. This research employs a qualitative approach using a case study method at TK Umara Kids, Pekanbaru. The subjects of the study consist of two teachers working in the classroom. Data were collected through observation, interviews, and documentation. The results of the study indicate that the teachers have implemented various strategies to improve their pedagogical competence. 5K principle (Agreement, Commitment, Consistency, Continuity, Consequence), implemented differentiated learning according to children's characteristics, and reflected on learning activities. Teachers also underutilize simple digital media such as educational videos, and their digital literacy skills still need to be improved. The conclusion of the study shows that the teachers' strategies in improving pedagogical competence through differentiated learning are good, but aspects of technology and collaboration with parents need to be strengthened to support successful learning